2019
DOI: 10.1111/jhn.12653
|View full text |Cite
|
Sign up to set email alerts
|

The barriers and enablers to achieving adequate calcium intake in young adults: a qualitative study using focus groups

Abstract: Background Despite the established benefits of calcium consumption, many young Australians are not meeting the recommendations for calcium intake. This is concerning because an adequate calcium consumption is important throughout young adulthood to reach peak bone mass and for the prevention of osteoporosis. Therefore, the present study aimed to explore the barriers and enablers to consuming calcium‐rich foods with young adults. Methods Using a semi‐structured question guide, five focus group discussions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Comparable studies in other countries reported similar findings of low calcium intakes in young women [25,26,28]. Reasons for poor calcium intakes in this group may be due to limited knowledge of the beneficial role of calcium for bone health in young adulthood [31,32], ethical considerations related to the dairy industry and farming practices [32], the perceived high cost of dairy products [32,33] resulting in calcium-rich foods being less accessible for students, the perception of dairy foods as fattening [34], and that this population group commonly practices restrictive eating, which might result in reduced consumption of dairy foods, affecting calcium intake. Some limitations of the dietary analysis should be noted.…”
Section: Discussionmentioning
confidence: 64%
“…Comparable studies in other countries reported similar findings of low calcium intakes in young women [25,26,28]. Reasons for poor calcium intakes in this group may be due to limited knowledge of the beneficial role of calcium for bone health in young adulthood [31,32], ethical considerations related to the dairy industry and farming practices [32], the perceived high cost of dairy products [32,33] resulting in calcium-rich foods being less accessible for students, the perception of dairy foods as fattening [34], and that this population group commonly practices restrictive eating, which might result in reduced consumption of dairy foods, affecting calcium intake. Some limitations of the dietary analysis should be noted.…”
Section: Discussionmentioning
confidence: 64%
“…Another Australian study looked into barriers and enablers into achieving adequate calcium intake in young adults. They found that young adults had limited knowledge of sources, prevention of disease and recommended amounts (2). Our findings of this study supported this as students lacked knowledge on alternative sources of calcium apart from dairy and vegans faced a huge barrier in keeping their calcium sources adequate as they lacked knowledge on alternative sources.…”
Section: Adolescents and Bone Health: The Importance Of This Worksupporting
confidence: 77%
“…We chose to do this study because few studies have been conducted to date, looking into attitudes of young adolescents that might result in better bone health. A Canadian qualitative study was recently conducted which looked into barriers and enablers for achieving adequate calcium intake in young adults (2).…”
Section: Introduction To Thesis Topic: Study Rationalementioning
confidence: 99%
“…A qualitative study with five focus-group discussions conducted with 39 youth (M=22.5±1.8 years, 75% girls) raised the issue of lactose intolerance and participants recognized that their friends placed themselves on dairy-free diets without seeking any medical advice. In particular, females reported that dairy products made them feel "really full" or "not too great" [28]. Hence, the current trends on diets for weight loss and/or other physical health goals, i.e., dairy-free and/or lactose-free diets, might have influenced the decrease on the intake of dairies products.…”
Section: Discussionmentioning
confidence: 99%